2022
DOI: 10.1002/pon.6062
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a novel pilot support group on distress and quality of life in breast cancer patients in Nigeria

Abstract: Objective To assess the effect of a new breast cancer support group (BCSG) on breast cancer patients' self‐reported distress and quality of life. Methods A single arm pre‐post trial providing an eight session healthcare provider led BCSG. Primary outcome variables were distress and quality of life assessed using the National Comprehensive Cancer Network Distress Thermometer (DT) and The Functional Assessment of Cancer Therapy ‐ Breast plus Arm Morbidity (FACT‐B+4), respectively. Topics in each session addresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
(33 reference statements)
0
1
0
2
Order By: Relevance
“…Os resultados deste estudo enfatizam a necessidade de uma abordagem integrada no tratamento do câncer de mama, que leve em consideração não apenas a dimensão física, mas também as implicações psicológicas e sociais (Asuzu et al, 2022). O apoio psicológico contínuo, juntamente com programas de educação e conscientização, são elementos fundamentais para promover o bem-estar geral das pacientes (Akechi et al, 2020).…”
Section: Resultsunclassified
“…Os resultados deste estudo enfatizam a necessidade de uma abordagem integrada no tratamento do câncer de mama, que leve em consideração não apenas a dimensão física, mas também as implicações psicológicas e sociais (Asuzu et al, 2022). O apoio psicológico contínuo, juntamente com programas de educação e conscientização, são elementos fundamentais para promover o bem-estar geral das pacientes (Akechi et al, 2020).…”
Section: Resultsunclassified
“…Os resultados deste estudo enfatizam a necessidade de uma abordagem integrada no tratamento do câncer de mama, que leve em consideração não apenas a dimensão física, mas também as implicações psicológicas e sociais (Asuzu et al, 2022). O apoio psicológico contínuo, juntamente com programas de educação e conscientização, são elementos fundamentais para promover o bem-estar geral das pacientes (Akechi et al, 2020).…”
Section: Resultsunclassified
“…Psychosocial research included in this Special Issue identifies individual resiliency factors, such as self-compassion, in patients with cancer in Xi'An, China 19 and pilot studies are reported demonstrating the feasibility of written exposure therapy for posttraumatic stress disorder in Iranian women with breast cancer 20 and of acceptance and commitment therapy for parents of children with a haematological malignancy or a solid tumour. 21 Asuzu et al 22 report a pilot psychosocial intervention group in Nigeria that shows potential in supporting breast cancer patients. However, the need for greater attention to interventional research in psychosocial oncology was highlighted by Onyeka et al 13 in a scoping review of the psychosocial aspects of cancer in sub-Saharan Africa.…”
Section: Overview Of the Special Issue Contentmentioning
confidence: 99%